2004
DOI: 10.1097/01.tp.0000113467.36269.f8
|View full text |Cite
|
Sign up to set email alerts
|

Donor heme oxygenase-1 genotype is associated with renal allograft function1

Abstract: Our data suggest an influence of the HO-1 gene promoter polymorphism on kidney allograft function and thus support previous studies indicating a protective effect of HO-1 induction in organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
2
37
0
4
Order By: Relevance
“…Kidney function from donors with at least one short GTrepeat (S allele) was improved compared with donors with long GT-repeats. Results from multivariate analysis, controlling for a variety of parameters, showed that serum creatinine of recipients, who received a graft from S allele carriers, was 0.81 times that of noncarriers (95% confidence interval [CI]: 0.70-0.95, p = 0.01) (40). No difference was found between the two groups for rejection or delayed graft function.…”
Section: Interstitial Renal Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…Kidney function from donors with at least one short GTrepeat (S allele) was improved compared with donors with long GT-repeats. Results from multivariate analysis, controlling for a variety of parameters, showed that serum creatinine of recipients, who received a graft from S allele carriers, was 0.81 times that of noncarriers (95% confidence interval [CI]: 0.70-0.95, p = 0.01) (40). No difference was found between the two groups for rejection or delayed graft function.…”
Section: Interstitial Renal Diseasementioning
confidence: 91%
“…GT-repeat length polymorphisms in the HO-1 promoter correlate with renal function post-transplantation in humans (40). Kidney function from donors with at least one short GTrepeat (S allele) was improved compared with donors with long GT-repeats.…”
Section: Interstitial Renal Diseasementioning
confidence: 99%
“…The two most prevalent haplotypes were A(-413) (GT) 29 and (-413) T (GT) 22 indicating that the 'favorable' A-allele is in LD with the 'unfavorable' class L genotype. The LD measures D and r 2 were 0.87 and 0.50, respectively, indicating strong LD between the two promoter polymorphisms.…”
Section: Are the Two Ho-1 Polymorphisms In Linkage Disequlibrium?mentioning
confidence: 99%
“…It has been hypothesized that recipients who are carriers of the short allele or who receive a kidney from a donor who carried the short allele variant of the (GT) n polymorphism may have improved graft outcomes due to a beneficial increase in HO-1 expression. Clinically, in renal transplantation, both the 1-year serum creatinine level and 5-year graft survival were reported to be significantly better when the donor was an S-allele carrier (17,18). However, donor upregulation of HO-1 did not prevent clinically significant graft injury (delayed graft function (DGF) or acute rejection (AR)), and the response to injury was inconsistent with a survival benefit in grafts experiencing AR but not DGF.…”
Section: Introductionmentioning
confidence: 99%
“…PCR amplification was performed in 10 lL reactions using 0.625 units of HotStar Taq polymerase (Qiagen, Valencia, CA). Specific primers (forward: 5 -AGA GCC TGC AGC TTC TCA GA-3 ; reverse 5 -ACA AAG TCT GGC CAT AGG AC-3 ), previously designed by Exner and colleagues (17), were modified with a 5 -FAM label on the forward primer (Invitrogen, Carlsbad, CA). The reaction utilized 2 lL template DNA, 1 lL 5 lM for- One microlitre of diluted PCR product was added to 10 lL of HiDi formamide plus GeneScan 500 LIZ size standard (both from Applied Biosystems, Foster City, CA).…”
Section: Genotyping Of Variable Length Polymorphism (Gt) Nmentioning
confidence: 99%